2020
DOI: 10.1155/2020/1954398
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Role of Inflammation and Oxidative Stress on Age-Related Cardiovascular Diseases

Abstract: The global population above 60 years has been growing exponentially in the last decades, which is accompanied by an increase in the prevalence of age-related chronic diseases, highlighting cardiovascular diseases (CVDs), such as hypertension, atherosclerosis, and heart failure. Aging is the main risk factor for these diseases. Such susceptibility to disease is explained, at least in part, by the increase of oxidative stress, in which it damages cellular components such as proteins, DNA, and lipids. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 277 publications
(304 reference statements)
2
63
0
8
Order By: Relevance
“…Conversely, the rising leptin levels in the heart positively correlate with coronary artery disease, left ventricular hypertrophy, stroke, and myocardial infarction ( Soderberg et al., 1999 ; Wallace et al., 2001 ; Chait and den Hartigh, 2020 ). Along with pro-inflammatory circulating signals, a transcription factor, NF- κ B, is a product of chronic inflammation in cardiovascular tissue and is a useful clinical indicator for obesity-related inflammation ( de Almeida et al., 2020 ).…”
Section: Oxidative Stress In Obesity and Associated Comorbiditiesmentioning
confidence: 99%
“…Conversely, the rising leptin levels in the heart positively correlate with coronary artery disease, left ventricular hypertrophy, stroke, and myocardial infarction ( Soderberg et al., 1999 ; Wallace et al., 2001 ; Chait and den Hartigh, 2020 ). Along with pro-inflammatory circulating signals, a transcription factor, NF- κ B, is a product of chronic inflammation in cardiovascular tissue and is a useful clinical indicator for obesity-related inflammation ( de Almeida et al., 2020 ).…”
Section: Oxidative Stress In Obesity and Associated Comorbiditiesmentioning
confidence: 99%
“…More importantly, NF-κB also possesses the ability to regulate the expression activity of NOX1, via binding its element in the promoter of NOX1 [27] and it is mainly activated by TNF-α [28] . Additionally, increasing evidence indicated that there is a crosstalk between Nrf2 and NF-κB [29,30] . Thus, NF-κB might participate in the downregulation of Nrf2 on the expression of NOX1 and the level of oxidative stress in T 2 AECs induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic low-grade, systemic and local inflammation that develops during obesity links obesity to the development of insulin resistance (Gregor and Hotamisligil 2011 ), which then effects a variety of different organs involved in the control of metabolic homeostasis, including adipose tissue, liver, endocrine pancreas, hypothalamus, and possibly skeletal muscle. As adipocytes are a known source of pro-inflammatory cytokines, including TNF-α, IL-1, and IL-6, obesity can be seen as a chronic inflammatory condition (de Almeida et al 2020 ; Franssen et al 2016 ; Schmidt-Lucke et al 2015 ). These cytokines are known potent stimulators of the production of ROS and NOS by macrophages and monocytes and thereby increasing oxidative stress.…”
Section: Inflammation In Heart Failurementioning
confidence: 99%